THE CHARACTERISTIC FORMATION OF INSPIRATION GROUP IN ASEAN ECONOMIC COMMUNITY (AEC) - Susanti Susanti; Eka Aprilia Mardiansyah; Dimas Fahrudin (Proceedings Education and Language International Conference, 2017)
The era of the ASEAN Economic Community (AEC) is a challenge and an opportunity for the Indonesian. The impact of the MEA is not only in the economic sector but also all sectors for example like international communication and education. All sectors must be prepared to deal with the implementation of the AEC. One need to be prepared is the quality of Human Resources. In this case, improving the quality of human resources can be prepared through education, particularly at universities. The efforts of student preparation in order to be prepare for contribution in MEA can be done by forming groups of study which based on characters, this group of studycalled inspiration group. In the inspiration Group, each group will give some information about EAC by forming their characters. The method that used in this research were sharing, discussions, mini research, and speech in English about Indonesian culture. The characteristic formation that demand in this group were competitive, independent character, hardworking, high nationalism, and the most importance thing is international communication. Keywords:  Characters, formation, groups, MEA, students